1992
DOI: 10.1080/02724936.1992.11747614
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia and the inappropriate ADH syndrome in pneumonia

Abstract: We studied serum sodium, plasma osmolality and urinary sodium and osmolality on days 1, 3 and 5 of hospitalization of 100 children aged from 1 month to 12 years admitted with a diagnosis of pneumonia. Hyponatraemia (serum sodium concentration < or = 130 mmol/l) was found in 31 patients at the time of admission. The probable cause of hyponatraemia in 94% of cases was the syndrome of inappropriate antidiuretic hormone secretion (SIADH). Symptoms and signs indicative of severe pneumonia were two to three times mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 8 publications
6
90
0
3
Order By: Relevance
“…There have been several reports regarding HN in children with pneumonia [1][2][3][4], including the study by Don et al In those studies the authors speculated that the mechanism of HN in pneumonia is due to the syndrome of inappropriate antidiuretic hormone (ADH) secretion and found that HN was associated with the severity in pneumonia. In addition, we here would like to suggest that the deeper the site of inflammation in the respiratory tract, the higher the prevalence of HN in children with RTIs.…”
Section: Sirsmentioning
confidence: 99%
“…There have been several reports regarding HN in children with pneumonia [1][2][3][4], including the study by Don et al In those studies the authors speculated that the mechanism of HN in pneumonia is due to the syndrome of inappropriate antidiuretic hormone (ADH) secretion and found that HN was associated with the severity in pneumonia. In addition, we here would like to suggest that the deeper the site of inflammation in the respiratory tract, the higher the prevalence of HN in children with RTIs.…”
Section: Sirsmentioning
confidence: 99%
“…It occurs in around one-third of children hospitalised with CAP [26], the mechanism for which remains unclear, and is associated with higher inflammatory markers [27] and poorer outcomes [26]. Severe hyponatraemia can cause confusion or seizures and for this reason fluid restriction (between 50% and 66% of maintenance) is recommended in children with CAP and hyponatraemia who are haemodynamically stable and not dehydrated [28].…”
Section: Syndrome Of Inappropriate Antidiuretic Hormone Secretionmentioning
confidence: 99%
“…9 One study has shown an association between the severity of pneumonia in children and the development of hyponatremia due to SIAD. 10 To our knowledge, there have been no studies evaluating the impact of different causes of hyponatremia on mortality in elderly patients with aspiration pneumonia.…”
mentioning
confidence: 99%